Medición de usabilidad de una aplicación móvil de cancionero en idioma kichwa corriente - Vega Quiroz, Clovis (2022)
The objective of this study is the creation and evaluation of the usability of a mobile songbook application in the current Kichwa language. The research focus is applied in nature, with an emphasis on application design. A group of 15 users constituted the study population for this project. The collection of information about usability is based on the SUS (System Usability Scale) questionnaire, which is a reliable and fast tool to measure usability, which is made up of 10 questions, the answers were evaluated using a scale of Likert of 5 points to measure the evaluation of the participants. The information processing was carried out statistical tables and graphs made in Excel that allowed a better analysis of the data collected through the usability questionnaire in order to determine the correct functioning of the system and reach the pertinent conclusions, in addition to verifying the hypothesis. raised. The usability of a current Kichwa language songbook mobile application (AMCIKC) is satisfactory, efficient and effective.